#TITLE_ALTERNATIVE# - FITRIA NIM: 10313010, RICHA
Newton's law of gravity and Einstein's General Theory of Relativity are well established in explaining various daily and astronomical phenomena. However, there exist some problems that remain unexplained by these two theories of gravity. One of them is the problem of mismatch between luminous and dynamic mass which then triggers the proposed additional mass component called dark matter. Various astrophysical phenomena have been tried to be explained by adding this unseen dark matter, among them is the flat rotation curves of spiral galaxies. Unfortunately, dark matter has never been convincingly detected so far. Therefore, some physicists proposed alternative theories without involving dark matter in the scenarios. The most reasonable alternative theory is to modify the theory of gravity itself. One of the modified gravity theories that have been proposed and will be discussed in this Final Project is the Theory of Emergent Gravity (EG) by Erik Verlinde. EG claims that gravity is not a fundamental force, but instead a force derived from the law of thermodynamics, that is nothing but an entropic force. EG also explains that dark matter is only an additional effect of gravity resulting from the creation of baryonic matter through removal of dark energy entropy. In this Final Project the author examined the validity of EG theory on galaxy level by fitting rotation curves of spiral galaxies. As a comparison, fitting procedures were also performed with MOND. The fitting method used here is the Metropolis Hastings Monte Carlo Markov-Chain (MCMC). Fitting is performed to find the best ratio parameter of 𝑀/𝐿 disk and bulge mass density,𝜌𝑅𝑒 for galaxy with bulge component. In general, EG is better in explaining the rotation curves of galaxies with considerable bulge and decreasing rotation curves at large radius from the center, whereas MOND fits to galaxies that have only disc component and flat rotation curves.